Hereditary angioedema type III (estrogen-dependent) report of three cases and literature review* - Amanda Rodrigues Miranda; Ana Paula Fusel de Ue; Dominique Vilarinho Sabbag; Wellington de Jesus Furlani; Patrícia Karla de Souza; Osmar Rotta (Sociedade Brasileira de Dermatologia, 2013)
In this article, three cases of hereditary angioedema (HAE) type III (estrogen-dependent or with normal C1 inhibitor) are reported. The HAE was initially described in women of the same family in association with high-leveled estrogenic conditions such as the use of oral contraceptives and pregnancy. There is no change in the C1 inhibitor as happens in other types of hereditary angioedema, and mutations are observed in the encoding gene of the XII factor of coagulation in several patients. The current diagnosis is mainly clinical and treatment consists in the suspension of the triggering factors and control of acute symptoms. A brief review of physiopathology, clinical features, genetic alterations and treatment are also presented.